Faktor-Faktor yang Memengaruhi Keberhasilan Adopsi E-Commerce pada Perum BULOG - AJI, PRAWOKO SETYO; Jangkung Handoyo Mulyo (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2023)
E-commerce is a major force in driving the world's digital economy. Indonesia has an important role in developing e-commerce, especially in Southeast Asia. However, several organizations in Indonesia have experienced difficulties in the process of the e-commerce adoption stage, which often leads to failure. This paper aims to predict the factors that influence e-commerce adoption. The quantitative research method was used to test the hypothesis statistically (SEM-PLS). TOEI model (TOE framework and individual context of UTAUT theory) proposed to predict the factors that influence the e-commerce adoption by Perum BULOG. It was found that the technology context (relative advantage, compatibility, and complexity) positively affected e-commerce adoption. So, organizations need to consider technology as a main predictor and accelerator in the success of the e-commerce adoption stage. The other contexts (organizational, environment, and individual) were found to have no relationship with e-commerce adoption.